Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan, dan Kepercayaan terhadap Minat Nasabah Menggunakan Muamalat Digital Islamic Network di Bank Muamalat KCP Madiun - Fatin Alfiah Rahmah; Husna Ni’matul Ulya (Mutanaqishah: Journal of Islamic Banking, 2023)
The use of digital transactions is still relatively low in Indonesia, along with the low number of uses of Muamalat DIN at Bank BMI KCP Madiun along with the increasingly attractive features in Muamalat DIN. Of the many studies on the use of banking technology, this research is a research development from previous studies using the Technology Acceptance Model theory. The purpose of this study was to examine the effect of perceived usefulness, perceived ease of use, and partial or simultaneous trust on customers' interest in using Muamalat DIN at BMI KCP Madiun.The method used in this study is a quantitative method by collecting questionnaire data distributed to customers of Bank Muamalat KCP Madiun. The sample of this research was 95 respondents who were taken by incidental sampling technique. Methods of data analysis using multiple linear regression test, classic assumption test, hypothesis testing (t test and F test), which then the data is processed using the IBM SPSS Statistics 25 application.The results of the t test show that the perceived benefit variable has a t_count value of 0.882 <1.986 so that the perceived benefit has no effect on interest, the perceived ease of use variable has a t_count value of 3.698 > 1.986 so the perceived ease of use has a significant positive effect on interest, the trust variable has a t_count of 4.065 > 1986 so that trust has a significant positive effect on interest. Based on the F test it is known that f_count is 30.395 <3.098 so it can be concluded that perceived usefulness, perceived ease of use, and trust simultaneously have a positive and significant effect on intention to use.